2021
DOI: 10.3390/cancers13215390
|View full text |Cite
|
Sign up to set email alerts
|

An HLA-A*11:01-Binding Neoantigen from Mutated NPM1 as Target for TCR Gene Therapy in AML

Abstract: Acute myeloid leukemia (AML) is a hematological malignancy caused by clonal expansion of myeloid progenitor cells. Most patients with AML respond to chemotherapy, but relapses often occur and infer a very poor prognosis. Thirty to thirty-five percent of AMLs carry a four base pair insertion in the nucleophosmin 1 gene (NPM1) with a C-terminal alternative reading frame of 11 amino acids. We previously identified various neopeptides from the alternative reading frame of mutant NPM1 (dNPM1) on primary AML and iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…For example, Lee et al reported a novel InDel within the KIT gene, a commonly mutated gene in AML patients, in a clinical sample from a 35 year old female [64]. Two neoantigens derived from NPM1 mutations have been identified [65, 66]. Variant calling was performed on TCGA-LAML samples using a consensus approach in which each variant had to be detected by at least two separate variant callers (for SNVs) or three separate variant callers (InDels) to be considered.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Lee et al reported a novel InDel within the KIT gene, a commonly mutated gene in AML patients, in a clinical sample from a 35 year old female [64]. Two neoantigens derived from NPM1 mutations have been identified [65, 66]. Variant calling was performed on TCGA-LAML samples using a consensus approach in which each variant had to be detected by at least two separate variant callers (for SNVs) or three separate variant callers (InDels) to be considered.…”
Section: Resultsmentioning
confidence: 99%
“…CD33 is expressed in the majority of leukemic blasts, but the driver mutation dNPM1 is only found in approximately 30% of all AML patients. 18 , 19 Although another dNPM1-TCR specific for HLA-A∗11:01 has already been described, 44 further expansion of the available dNPM1-TCR selection is required to enable flexible therapy adjustments according to the patient’s HLA haplotype.…”
Section: Discussionmentioning
confidence: 99%
“…Tetramer-positive CD8+ T cells were isolated and their activity towards primary AMLs investigated. The TCR was then isolated from a clone with high anti-leukemic reactivity and its capability to specifically recognize and lyse HLA-A*02:01-positive ΔNPM1 AML demonstrated after retroviral transduction of CD8+ and CD4+ T cells [145]. Moreover, T cells transduced with TCR for HLA-A*02:01-binding CLAVEEVSL efficiently killed AML cells and prolonged OS of NSG mice engrafted with HLA-A*02:01-positive NPM1-mutated OCI-AML3 human cells [145] (Fig.…”
Section: Antibodies Against Cd33 and Cd123mentioning
confidence: 99%